Measurement of several qualitative traits and body size of Lombok Muscovy Ducks (Cairina moshcata) in semi-intensive rearing - Tamzil, M.H.; Lestari, L.; Indarsih, B. (Journal of the Indonesian Tropical Animal Agriculture, 2018)
The study was conducted to identify phenotypic characteristics of Lombok Muscovy ducks. A total of 100 adult male and 100 adult female Muscovy ducks. The research location was determined by purposive random sampling, while the determination of farmers and Muscovy ducks was done incidentally. Observations were made on each Muscovy duck by observing the color, body weight and size of body parts. The body size data were tabulated, averaged, and then analyzed descriptively; meanwhile, the plumage color data were calculated in frequency. To find the relation between size of body parts and body weight, data were analyzed using simple regression. The study found that the male Muscovy ducks had two plumage characteristics, consisting of white and black-white, both shared the same frequencies, while in the female Muscovy ducks, white color was more dominant compared to the black-white color. The colors of the beak were divided into two i.e., black with a white color in the middle and reddish-white with pink colors in the middle. The size of Lombok Muscovy ducks was rather small in comparison with the other Muscovy ducks. The size of male duck was larger than that of the female.